Adult Attachment and Dyadic Adjustment: The Mediating Role of Shame - Martins, Teresa C. (2016)
Although it is widely recognized that adult attachment is associated with romantic relationship quality, the mechanisms involved remain poorly understood. This study aimed to investigate the mediating role of external and internal shame on the association between attachment and dyadic adjustment. A battery of self-report measures was completed by 228 Portuguese participants and a serial multiple mediation model was tested. Data showed that, in the population under study, attachment dimensions were associated with worse dyadic adjustment through high external and internal shame. Internal shame alone also mediated the association between attachment avoidance and dyadic adjustment. This study identifies a new putative mechanism linking adult attachment and intimate relationship functioning that may be targeted in couples therapy to promote a better dyadic adjustment and relationship functioning.